Maintenance and facilities management of Kota Putera Square (KPS) / Mohamad Zuhairi Effendy - Effendy, Mohamad Zuhairi (Universiti Teknologi MARA UiTM,Perak, 2021)
Practical training is a semester-long training programme for students who are nearing the end of their studies. This training is intended to help the student become acquainted with the working environment. In order to graduate from the university, it is also necessary to finish all of the courses studied. Every student may benefit from this training, implying that the working environment may offer the student an understanding of how real- world work is done, which will be valuable in the future.